In silico comparative study of Zika Virus Proteins and analysis of Membrane glycoprotein M as a candidate for vaccine design - Nowshen, Afia (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.